2011
DOI: 10.1007/s10126-011-9417-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein Gene Family of the Porphyra seriata and Enhancement of Heat Stress Tolerance by PsHSP70 in Chlamydomonas

Abstract: Heat shock proteins and molecular chaperones are key components contributing to survival in the abiotic stress response. Porphyra seriata grows on intertidal rocks exposed to dynamic environmental changes associated with the turning tides, including desiccation and heat stress. Analysis of the ESTs of P. seriata allows us to identify the nine HSP cDNAs, which are predicted to be PsHSP90, three PsHSP70, PsHSP40 and PsHSP20, and three 5'-truncated HSP cDNAs. RT-PCR results show that most of the PsHSP transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Multiple alignments and bioinformatics analysis results showed that the deduced BcHSP70 had high similarity to other plant HSP70s and had the clearest relationship to AtHSP70-4. Deduced BcHSP70 protein of the isolated BcHSP70 cDNA exhibited conserved motif and domains with reported HSP70s from other reported plant such as A. thaliana and N. tabacum (Lin et al 2001;Cho and Hong 2004), which indicated that those domains are very important for maintaining the function of HSP (Guy and Li 1998;Montero-Barrientos et al 2010;Park et al 2012). In addition, BcHSP70 possessed a cytosolic compartment sequence, GPKIEEVD, at the C-terminal (Boorstein et al 1994;Guy and Li 1998;Tom et al 1999), suggesting that BcHSP70 may be located in the cytosolic region.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Multiple alignments and bioinformatics analysis results showed that the deduced BcHSP70 had high similarity to other plant HSP70s and had the clearest relationship to AtHSP70-4. Deduced BcHSP70 protein of the isolated BcHSP70 cDNA exhibited conserved motif and domains with reported HSP70s from other reported plant such as A. thaliana and N. tabacum (Lin et al 2001;Cho and Hong 2004), which indicated that those domains are very important for maintaining the function of HSP (Guy and Li 1998;Montero-Barrientos et al 2010;Park et al 2012). In addition, BcHSP70 possessed a cytosolic compartment sequence, GPKIEEVD, at the C-terminal (Boorstein et al 1994;Guy and Li 1998;Tom et al 1999), suggesting that BcHSP70 may be located in the cytosolic region.…”
Section: Discussionmentioning
confidence: 88%
“…For example, HSP70 was found necessary for heat stress tolerance in Arabidopsis thaliana (Su and Li 2008). Introduction of HSP70 from Porphyra seriata into Chlamydomonas can effectively enhance the latter's tolerance to heat stress (Park et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When the rice mitochondrial HSP70 gene ( mtHsp70 ) was constitutively expressed in rice suspension culture cells, heat stress proved less potent in inducing apoptosis [22]. The heterologous expression of the Porphyra seriata mitochondrial gene PsHSP70b in Chlamydomonas improved survival and cell growth under heat stress conditions [23]. Drought stress tolerance proved also to be enhanced when NtHSP70-1 was over-expressed [24].…”
Section: Resultsmentioning
confidence: 99%
“…HSPs play an essential role in protecting cells, regulating nascent protein folding and translocation, refolding of denatured proteins, and the disassembly of protein aggregates under both stressed and non-stressed conditions (Bray et al 2000;Feder and Hofmann 1999;Schroda and Vallon 2009). Under stress conditions, HSP70s are upregulated, participate in the refolding of denatured proteins, maintain cell homeostasis, and protect organisms against damage (Mayer and Bukau 2005;Park et al 2011). A previous report shows that an HSP70 from P. seriata responds to high temperature and is involved in thermotolerance .…”
Section: Identification Of Degs Under Abiotic Stress Conditionsmentioning
confidence: 98%